Legacy issues in post-pine (Pinus pinaster) restoration environments: Weeds compromise seedling growth and function more than edaphic factors - Stanbury, K.; Stevens, Jason; Ritchie, Alison (John Wiley & Sons Ltd., 2018)
Restoration of commercial pine plantations to native ecosystems is increasing globally. This study investigated the abiotic and biotic factors in a postpine (Pinus pinaster) ecosystem that could potentially limit successful restoration of highly biodiverse Banksia woodlands. Soil abiotic conditions were analysed across a 7-year postpine chronosequence and compared with a reference Banksia woodland soil to assess soil legacy issues. Ten native species were grown in postpine soils and monitored for germination and growth responses. Three species were selected and grown in the presence of an invasive species, Ehrharta calycina, to assess biotic impacts on seedling emergence, establishment, physiology, and drought response. Analysis revealed no differences in soil abiotic conditions along the chronosequence in comparison with the reference soil, apart from increasing organic carbon along the chronosequence (p =.003). Germination was not impeded in postpine soils, but seedling growth responses varied among species and soils. Seedling emergence was not affected by the presence of E. calycina; however, seedling growth measurements were significantly reduced (20%–78% decline). Physiological function (stomatal conductance) of native seedlings prior to drought treatment was not impeded, though when grown with E. calycina under drought 2 species, Banksia menziesii and Corymbia calophylla, exhibited a more rapid loss of physiological function. This case study examines abiotic and biotic limitations to Banksia woodland restoration success in postpine environments, suggesting postpine soils are not a barrier to restoration, and highlight the importance of preventing E. calycina from becoming established.